The influence of prestige bias on knowledge and the dynamics of cultural transmission about medicinal plants in local medical systems - Dantas, Janilo; André Luiz Borba do Nascimento; Taline Cristina da Silva; Ulysses Paulino Albuquerque; Elcida de Lima Araújo (Ethnobotany Research and Applications, 2025)
Background: Cultural transmission is crucial in social-ecological systems like local medical systems. According to the Theory of Cultural Evolution (CE), the information transmitted can change, either through cultural mutations (random) or guided variations (intentional). In local medical systems, this cultural transmission can be selective. For example, individuals tend to replicate information from prestigious social models, who generally have specialized knowledge in the area of interest. This phenomenon is known as "Prestige Bias". This study investigated how prestige bias affects knowledge and cultural transmission dynamics related to medicinal plants in local medical systems. The hypotheses tested were: H1: prestigious individuals have more knowledge about medicinal plants than those less prestigious; H2: information about medicinal plants from prestigious sources is less prone to cultural mutations than information from less prestigious sources; and H3: prestigious individuals promote more guided variation than cultural mutation. Methods: We examined the local medical system in the community of Lagoa do Junco, in Santana do Ipanema, Alagoas. We collected data through semi-structured interviews with 120 community residents and analyzed them using the Wilcoxon -Mann-Whitney test and a Generalized linear mixed model (GLMM) in the R development environment.Results: People recognized as prestigious have greater knowledge about medicinal plants. However, we did not observe a significant influence of prestige bias on reducing cultural mutations. Furthermore, it was found that prestigious individuals promote more guided variation than cultural mutation. Conclusions: This study reveals that prestige directly influences the dynamics of cultural evolution in local medical systems. Keywords: Cultural evolution, Copy errors, Ethnobotany, Medicinal plants